Alteration of fatty acid compositions in a starch-deficient mutant Arabidopsis thaliana (adg1-1) during seed development - Hasimah Alimon (Tanjong Malim, 2010)
Alteration of fatty acid compositions in a starch-deficient mutant Arabidopsis thaliana (adg1-1) during seed development by Hasimah Alimon